Determinants of household financial vulnerability in Malaysia and its effect on low-income groups / Abidullah Abida and Muhammad Hakimi Mohd Shafiai - Abida, Abidullah; Mohd Shafiai, Muhammad Hakimi (Universiti Teknologi MARA Selangor, 2018)
Household financial vulnerability is an important area of research in household economic studies. Hence, a number of studies have attempted to identify the factors that make households vulnerable to financial shocks. In Malaysia, the research is scant on this topic especially when it comes to low-income households. Therefore, the study aims to identify the macroeconomic factors that make the household vulnerable to financial shocks. For this purpose, the study uses the autoregressive distributed lag modelling approach as an estimation technique. The results revealed that household debt, prices of goods, interest rate and unemployment have a positive long-run relationship with household financial vulnerability while income has a negative relationship. Further analysis confirms that these predictors of financial vulnerability also affect the low-income groups. This study would be of interest to the academicians and policy makers in the area of household economics.